The Relationship Between Workload and Job Stress on Employee Turnover Intention at CV XYZ - Haerunisa Nanda Putri; Kartika Nuradina; Benny Bernadus (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
The high rate of employee turnover has become a major challenge for retail companies, including CV XYZ, as it affects productivity, cost efficiency, and organizational stability. This condition emphasizes the need to examine psychological factors that drive employees’ intention to leave their jobs. The present research explores how workload and job stress are associated with turnover intention among employees of CV XYZ. This research employed a quantitative methodology using multiple correlation. The sample comprised 90 respondents selected via stratified random sampling from a total population of 530 employees. The research instruments included the workload scale (NASA–TLX), job stress scale (Parker & DeCotiis, 1983) and turnover intention scale (Mobley, 1977). Data were analyzed using Spearman’s Rho correlation and multiple regression techniques. The findings reveal that workload and job stress are positively and significantly associated with turnover intention (p < 0.001, r = 0.603). These results are consistent with the Job Demands–Resources framework, Cognitive Appraisal Theory, and the Conservation of Resources approach, which suggest that stress and turnover intention result from an imbalance between work demands and available personal resources. Results are expected to provide insights for management in balancing workload, strengthening social support, and improving employees’ psychological well-being.